Informal Caregivers in Chile: The Equity Dimension of an Invisible Burden - Villalobos-Dintrans, P (Oxford University Press, 2019)
Population aging is driving a process of increase in long-term care needs in Chile and many countries around the world. In this context, this article asks about the consequences of this increase in informal caregivers, emphasizing the inequity issues arising from these changes. Using the CASEN 2017 survey, caregivers are identified and matched to people with long-term care needs. Results show that most caregivers are women, and a large fraction of them are also elderly; this is similar to what has been found previously in developed countries. Caregivers have fewer opportunities than non-caregivers, which translates into lower income-generating ability and higher poverty. The nature of these tasks creates a vicious cycle in which people get trapped with increasing needs and fewer resources to meet them. Important differences arise between caregivers and the rest of the population. Even more concerning is that these disparities are avoidable to some extent, adding an equity dimension to the problem. This emphasizes the need for the generation of policies that will support caregivers and meet their needs. © 2019 The Author(s) 2019. Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.